FUS affects circular RNA expression in murine embryonic stem cell-derived motor neurons - Lorenzo Errichelli (Nature Portfolio, 2017)
The RNA binding protein FUS functions in several RNA biosynthetic processes and has been linked to the pathogenesis of amyotrophic lateral sclerosis (ALS). Here the authors show that FUS controls back-splicing reactions leading to circular RNA (circRNA) production in stem cell-derived motor neurons and that ALS-associated FUS mutations affect the biogenesis of circRNAs.